Analisis Kekuatan Tekan pada Kampas Rem Bahan Limbah Cangkang Kerang Dara dan Fly Ash Batubara - Rifki Hardika Akbar; Dadan Ramdan (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study analyzes the potential use of cockle shell waste and coal fly ash as alternative raw materials in the production of composite brake pads. The high volume of industrial and fisheries waste, which has not been optimally utilized, encourages the exploration of environmentally friendly materials with adequate mechanical performance. The main focus of this research is the compressive strength of the produced brake pads, as this parameter is crucial for ensuring effective and safe braking performance. The method used includes the mixing and molding of composite materials with varying compositions of cockle shell and fly ash, followed by compressive strength testing according to standards. This study also takes into account the environmental impact of using waste as filler material, which is expected to reduce reliance on conventional materials and decrease waste that contaminates the environment. The results of the study are expected to provide empirical data on the potential of these two wastes as fillers in brake pad matrices and to identify the optimal formulation that provides the highest compressive strength. This study contributes to the development of sustainable braking materials and efforts to mitigate the environmental impact of waste, while also opening opportunities for the reuse of waste that has previously been poorly managed.